Significant Broadening of the Substrate Scope for the Hydrated Imidazoline Ring Expansion (HIRE) via the Use of Lithium Hexamethyldisilazide - Grintsevich, Sergey; Sapegin, Alexander; Krasavin, Mikhail (Synthesis, 2022)
Substrates that are insufficiently activated towards the hydrated imidazoline ring expansion (HIRE) process have been previously found to deliver exclusively the products of aminoalkyl side-chain ring expansion. Attempted reversal of the process by thermal activation towards HIRE failed. We have found that for such problematic substrates the HIRE-type ring expansion can be effectively achieved by applying lithium hexamethyldisilazide (LHMDS) in toluene. LHMDS is thought to promote intramolecular transamidation, which leads to ring-expanded 10- and 11-membered heterocyclic products in modest to good yields. The process significantly broadens the substrate scope amenable to the HIRE strategy.
Keywords: [1,4]diazepinones; [1,4]ox(thi)azepinones; fused imidazolinium moiety; hydrated imidazoline ring expansion; aminoalkyl sidechain incorporation; lithium hexamethyldisilazide; facilitated intramolecular transamidation